Chagas: On the Road to Timely Diagnosis and Treatment of Affected Persons (Actualizaciones en Sida e Infectología, 2022)
Chagas was first identified more than a hundred years ago and continues to be, according to the World Health Organization, a neglected tropical disease affecting from 6 to 7 million people around the world. It is an endemic disease in 21 Latin American countries, where it is vectorially transmitted to humans and other mammals mostly through the feaces of blood- feeding triatomine insects. The infection is generally asymptomatic, but 3 out of 10 patients may suffer from cardiac or digestive disorders. If detected on time and during its initial phase, cure or improved clinical progression of this disease is possible. As a health concern, it has historically been associated with poverty and the rural setting in Latin America, but it currently constitutes a global health concern that has gone beyond the region borders, and nowadays there are people affected by Chagas anywhere in the world. Certain data about this disease leave governments and health systems in the spotlight: 7 out of 10 persons are unaware that they are infected and less than 10% of the infected persons receive a timely diagnosis and are therefore treated. “To talk about Chagas,” as expressed by the NGO Hablemos de Chagas, means a lot more than just talking about a disease. It is a complex problem that needs to be addressed through an approach that extends beyond the limits of the biomedical area, and, to that end, multiple dimensions, such as the biological, environmental, economic, political, education, and sociocultural areas, need to be assessed. An approach that is exclusively based on health and biomedical research is incomplete and fragmented and fails to resolve the complex scenarios of Chagas. Comprehensive inter- and multidisciplinary work that considers the experience and background of the affected persons is required. In Argentina, there is an estimated 1.5 million people affected by Chagas, and the area having historical presence of the vector consists of 19 provinces, although 10 of those have achieved certification of the interruption of vectoral transmission interruption by the Pan American Health Organization. However, in the past few years, the epidemiology of Chagas in our country has changed and vertical transmission has become the route giving rise to the highest number of new cases per year (approximately 1300 babies are born with Chagas every year). Without overlooking surveillance and vector control, it is extremely important to bear in mind this scenario that extends throughout the Argentine territory. For several years, efforts have been made to draw increasing attention to Chagas. For that reason, since 2011, the National Day for Eradication of Chagas in Argentina is commemorated every last Friday of August (Argentine Law No. 26,945). This commemoration seeks to “promote community involvement and commitment, through joint efforts by the scientific, health, and school community, as well as by the community at large, to denaturalize the Chagas disease, to raise awareness about this problem, and to end the silence around this matter.” By our next National Day for Eradication of Chagas in Argentina, certain concerns will have been addressed, such as the regulatory framework of Law 26,281 through Executive Order No. 202/2022 published in the Official Gazzete. Under this law, which was passed in 2007 and lacked a regulatory framework for 15 years, the prevention and control of all forms of transmission of Chagas disease, from a cross-cutting approach to human rights, gender, and interculturality, has been declared as a “matter of national concern” and has been given priority in the National Health Policy of the Argentine Department of Health. Based on this regulations, there are several steps to be taken. For instance, the Mandatory Medical Program should be updated to include, in the list of provided services, diagnostic tests and comprehensive disease treatment for children, teenagers, and adults. Also, persons of childbearing potential and pregnant women should be examined to determine if they have Chagas and vertical transmission should be checked among all persons born to a positive pregnant person. The Argentine Department of Labor and Social Security should take the relevant measures to prohibit serological testing for the disease on any job candidates. The required financial resources should be adjusted to be able to fund programs conducting education, prevention, control, research, and treatment activities. Another recent major step forward is the implementation of genomic techniques by neonatal Chagas PCR in the diagnosis and treatment algorithms for the control of perinatal HIV, syphilis, hepatitis B, and Chagas infection, the EMTCT-PLUS initiative and the transfer of technology and training to all jurisdictions to provide greater access to diagnosis. Many challenges still lie ahead, such as vector monitoring in endemic rural areas as well as in the urban areas of San Juan, Mendoza, Catamarca, La Rioja and San Luis, and adequate communication about Chagas, which, as stated in the Department of Health’s General Guidelines for Chagas Communication Approach, “it is extremely important to re-think the most commonly used words, language, and images in order to revert practices that propagate stereotypes and outdated discourse, favoring stigmatization of the affected persons.” As a health team, we face greater challenges: to remove the medical, social, situational, and institutional obstacles hindering adequate diagnosis and treatment of affected persons, and, in particular, to prevent the loss of follow-up of babies born to positive pregnant persons. Additionally, affected persons should receive comprehensive primary care, by staff that is duly qualified to provide diagnosis and treatment, with adequate availability of supplies and medication. Prioritization of notifications to the National Health Surveillance System should also be established in order to obtain accurate information based on which rational decisions can be made with an impact on people’s health. A long road still lies ahead. We all need to get involved and promote actions at our workplace seeking to reduce the existing inequality regarding Chagas.